2022
DOI: 10.3390/app122412987
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in the Acceleration–Speed Profile of Elite Soccer Players: A Longitudinal Study

Abstract: This study aimed to describe the acceleration–speed (AS) profile of soccer players during competition and to analyse their seasonal changes and inter-player differences. The AS profile values (theoretical maximum acceleration (A0) and speed (S0)) of 14 elite soccer players were studied in 18 matches, which were divided into five season periods. The main findings showed the A0 (6.20 ± 0.51 m/s2) and S0 (9.18 ± 0.58 m/s) average team season values. Significant individual changes (p < 0.05 and effect size (Eta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Short sprints (≤10 m) and straight-line sprints are the most frequent movements preceding goal situations in soccer matches, with elite players exhibiting greater sprint distances and higher acceleration frequencies than non-elite players [6]. Recent research has shown that in both adult and youth players, explosive initial acceleration (≤20 m) during matches and sprint performance decline as the season progresses [7][8][9][10][11][12]. Therefore, repeatedly performing and improving explosive acceleration sprints throughout matches and seasons is a key factor for better performance.…”
Section: Introductionmentioning
confidence: 99%
“…Short sprints (≤10 m) and straight-line sprints are the most frequent movements preceding goal situations in soccer matches, with elite players exhibiting greater sprint distances and higher acceleration frequencies than non-elite players [6]. Recent research has shown that in both adult and youth players, explosive initial acceleration (≤20 m) during matches and sprint performance decline as the season progresses [7][8][9][10][11][12]. Therefore, repeatedly performing and improving explosive acceleration sprints throughout matches and seasons is a key factor for better performance.…”
Section: Introductionmentioning
confidence: 99%
“…Football is a complex and high physically demanding sport [1][2][3]. Analyses of physical demands in football are usually conducted through the quantification of physical performance, such as total distance, distance covered in different speed zones, and acceleration frequencies [4][5][6]. Research has shown that outfield players can cover 9-14 km during a match, covering from 5 to 15% of that distance at higher speeds [7][8][9].…”
Section: Introductionmentioning
confidence: 99%